Mediating roles of leaders toward sustainability trends of higher education institutions - Ayodele, Lasisi Abass (http://www.jocw.net, 2015)
Consistent awareness, integration and revisiting the missions for improvement towards sustainability of higher education need attention. Mediating roles of higher education institution leaders can enhance the improvement, through awareness on sustainable education and quality integration in administrative performance. Mediating roles of leader makes higher education institution (HEI) teaching-learning and administration activities effective for sustainable future. To achieve quality, effectiveness and efficiency, support of the HEI leaders as a mediator has effect on the survival for the fitness in higher education institution (HEI). This paper focuses on leadership roles and explores the literatures pertaining to leadership for sustainability of HEI. The study opines that there is relationship, importance connections between leadership and its roles for sustainability of HEI. The study discusses the possible roles of educational leadership towards sustainability of HEI. It revealed the advantages in managing HEI for future achievement. Keywords: Leadership, Mediating roles, Sustainability, Higher Education